2011
DOI: 10.1016/j.beproc.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Delay discounting and gambling

Abstract: Delay discounting describes the decline in the value of a reinforcer as the delay to that reinforcer increases. A review of the available studies revealed that steep delay discounting is positively correlated with problem or pathological gambling. One hypothesis regarding this correlation derives from the discounting equation proposed by Mazur (1989). According to the equation, steeper discounting renders the difference between fixed-delayed rewards and gambling-like variable-delayed rewards larger; with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
47
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 31 publications
11
47
1
Order By: Relevance
“…In addition, an earlier study by Eisenberger et al (1982) found that exposure to a variable long delay (average = 78 s) maintained self-control levels whereas exposure to a variable short delay (average = 5 s) increased levels of impulsivity. Furthermore, Madden et al (2011) assessed rats’ baseline levels of impulsivity followed by training on either a mixed delay schedule of short (either .01-s or 20-s) and long (either 20 or 60-s) intervals or a fixed delay that was associated with 50% LL choices from the impulsive choice task. The rats were then returned to an impulsive choice task in which they displayed a significant increase in LL choices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an earlier study by Eisenberger et al (1982) found that exposure to a variable long delay (average = 78 s) maintained self-control levels whereas exposure to a variable short delay (average = 5 s) increased levels of impulsivity. Furthermore, Madden et al (2011) assessed rats’ baseline levels of impulsivity followed by training on either a mixed delay schedule of short (either .01-s or 20-s) and long (either 20 or 60-s) intervals or a fixed delay that was associated with 50% LL choices from the impulsive choice task. The rats were then returned to an impulsive choice task in which they displayed a significant increase in LL choices.…”
Section: Introductionmentioning
confidence: 99%
“…These tasks require less inhibition of responding, as responding early only results in wasted effort rather than resulting in increased delays to reward, but the tasks are heavily linked with interval timing (Church et al 1998). The VI schedule was included as a comparison condition because previous interval exposure studies have used both fixed and variable delays (Eisenberger et al 1982; Madden et al 2011), but have not determined the relative efficacy of the two schedules in affecting choice and/or timing behaviors. The direct comparison of FI and VI schedules assessed whether any intervention effect was reliant on exposure to the specific intervals from the impulsive choice task (the FI intervention), or if exposure to the range of intervals around (and including) the SS and LL delays would also produce an intervention effect (the VI intervention).…”
Section: Introductionmentioning
confidence: 99%
“…This discounting of larger future rewards in favor of smaller immediate rewards is known as delay discounting (DD) and it is greater as the temporal distance between the immediate and delayed rewards increases (Bickel & Marsch, 2001). Higher DD rates have been associated with substance abuse, problem drinking, smoking, pathological gambling, and risky HIV behaviors (Bickel & Marsch, 2001; Bickel, Odum, & Madden, 1999; Kollins, 2003; Madden, Francisco, Brewer, & Stein, 2011; Vuchinich & Simpson, 1998). …”
mentioning
confidence: 99%
“…Behavior analysis has a strong record in discounting studies, and a potential for further development. Delay discounting has been thoroughly studied, and hyperbolic discounting of future events in various settings is a robust finding (Bickel & Marsch, 2001;Green & Estle, 2003;Green, Fristoe, & Myerson, 1994;Hantula & Bryant, 2005;Holt, Green, Myerson, & Estle, 2008;Kirby, 1997;Kirby & Herrnstein, 1995;Laibson, 1997;Madden, Francisco, Brewer, & Stein, 2011). Hyperbolic discounting is a discounting model that captures that we prefer things sooner rather than later, but it also captures the time-inconsistency and preference reversal.…”
Section: Methodsological Approachesmentioning
confidence: 99%